Hubungan Pemberian Asi Eksklusif Dengan Tidak Asi Eksklusif Terhadapperkembangan Anak Usia 3-12 Bulan - Hadi, Juli Zumia; , dr. Rusmawita, M.Kes.,Sp.A; , dr. D. Dewi Nirlawati (2015)
Background:Mother's Milk is a nutrient that is essential for the baby to support development.Exclusive breastfeeding breast milk is given to infants without the addition of any food and beverages except medicine and vitamins for 6 months.Breastmilk include omega 3, DHA, and AA have a role in optimizing the development of children who are aligned with the stimulation provided.The development is a process of someone in the act, to adapt to the environment and a custom in improving behavior to improve the competency of life. Objective: To identifythe relationship of exclusive breastfeeding to not breastfeeding exclusively on the development of children aged 3-12 months. Methods:The method used in this study was observational with cross sectional study design.Subject studies in children aged 3-12 monthsPosyandu health centers working area Karanggede, Boyolali district.Sampling using consecutive sampling with a sample of 60 children.Measuring instruments used in this study was a questionnaire exclusive breastfeeding and pre-screening questionnaire development.Data analysis using Chi-square test with the program as SPSS 22.0 for windows. Results: From the existing data on get results with p = 0.001 (p <0.05) and PR with a value of 0.133 (95% CI = 0.040 to 0.446). Conclusion:There is a relationship of exclusive breastfeeding with no exclusive breastfeeding on the development of children aged 3-12 months